We **complete the square** as we did in an earlier example above.

First, we collect the *x* parts together and the *y* parts together, then divide throughout by 3.

`3x^2+3y^2-12x+4=0`

`3x^2-12x+3y^2+4=0`

`x^2-4x+y^2+4/3=0`

Then we complete the square on the *x* part. We do not need to do so for the *y* part because there is no single *y* term (only a *y*^{2} term).

`(x^2-4x+4)+y^2+4/3=4`

`(x-2)^2+y^2=4-4/3`

`(x-2)^2+y^2=8/3`

So the circle has centre `(2,0)` and has radius `sqrt(8/3)~~1.63`.

Easy to understand math videos:

MathTutorDVD.com